Analisis Keindahan Janjang 1000 (Seribu): Tangga Bersejarah Ranah Minang di Nagari Sulit Air Kecamatan X Koto Diatas Kabupaten Solok - Syofitri, Rahmanuri; Novella, Tria; Reski, Dinda Sri; Ramawati, Agnes (TSAQOFAH, 2025)
Janjang 1000 in Nagari Sulit Air, Kecamatan X Koto Diatas, Solok Regency, is a historic staircase that embodies the rich cultural heritage of the Minangkabau community. This study aims to analyze the aesthetic meaning and historical value of Janjang 1000, focusing on its architectural design, cultural relevance, and potential development as a tourist destination. A qualitative method was employed through field observations and in-depth interviews with local residents and historians. The findings reveal that Janjang 1000 functions not only as a connecting pathway but also holds symbolic meanings related to resilience, solidarity, and the local wisdom of the Minangkabau people. The complexity of the staircase’s construction and its utilization in daily life reflect the integration of function, aesthetics, and cultural identity. However, modernization and a lack of preservation awareness pose challenges to sustaining these values. Therefore, this study recommends community-based preservation strategies and the development of sustainable tourism that maintains the integrity of local culture. By highlighting the aesthetic and historical values of Janjang 1000, this research reinforces the importance of cultural heritage preservation as part of Minangkabau’s identity and regional appeal.